Perubahan Bentuk Busur Abad VIII-XV Berdasarkan Relief Candi Jawa Tengah dan Jawa Timur - Setiawan, Irvan (JANUS, 2025)
The bow is an important instrument in the development of human civilization, including in the Indonesian archipelago. Its functions as a hunting tool, a weapon for warfare, and later as a means of sport and recreation have ensured its continued relevance across different historical periods. In the Indonesian Classical Period, its presence is represented in temple reliefs in Central and East Java. This study aims to examine the transformation of bow forms from the 8th to the 15th centuries CE based on temple relief representations. The data were collected from archery scenes depicted in the reliefs of Borobudur, Prambanan, Penataran, Kedaton, Surawana, and Sukuh temples. The analysis applies chrono-typology and seriation to compare several attributes, namely the ratio of bow length to archer height, bow type, curvature, and decoration. The results show significant changes over time, including a reduction in size, a shift in the dominant type from vansa to saranga, a transformation of curvature from straight to reflex-deflex, and increasing variation in kotidhanus design. These transformations are influenced by technological, military, political, and economic factors. The findings also indicate that bows and arrows are part of a dynamic human–artifact interaction that contributes to cognitive development and collective learning processes. === Busur adalah perangkat yang tidak dapat dipisahkan dari perkembangan peradaban manusia, termasuk di wilayah kepulauan Indonesia. Fungsinya sebagai alat berburu, keprajuritan atau berperang hingga olahraga atau rekreasi membuat busur selalu memiliki peran tertentu dalam setiap zaman. Pada Zaman Klasik Indonesia, busur masih menunjukkan eksistensinya melalui berbagai relief candi di Jawa Tengah dan Jawa Timur. Untuk mengetahui bagaimana perubahan bentuk busur yang digambarkan pada relief candi dari zaman ke zaman maka perlu dilakukan penelitian. Penelitian dipusatkan pada relief adegan memanah pada Candi Borobudur, Prambanan, Penataran, Kedaton, Surawana dan Sukuh. Krono-tipologi dan seriasi disusun berdasarkan atribut busur yang akan dibandingkan, yaitu: rasio panjang busur dan tinggi pemanah, jenis busur, kurvatur serta dekorasi. Dari hasil analisis diketahui bahwa sepanjang abad ke-8 M hingga ke-15 M, busur di Jawa mengalami perubahan: ukuran memendek, mayoritas jenis vansa menjadi saranga, kurvatur lurus menjadi reflex-deflex, desain kotidhanus yang beragam. Faktor teknologi, militer, politik dan ekonomi menjadi pendorong utama perubahan yang terjadi. Hasil penelitian ini juga mengungkap bahwa busur panah memiliki dinamika interaksi dengan manusia sebagai agen pendorong perkembangan kognisi dan proses belajar kolektif.